Race, Racial Negativity, and Competing Conceptions of American National Identity. Issue 2 (March 2021) - Graeber, John; Setzler, Mark
This study explores differences among African Americans, Latinos, and whites regarding which attributes are most important to being truly American and how these competing conceptions relate to an individual's level of racial animus toward African Americans. Using nationally representative survey data, we first find that Americans of different races vary across six different components of national identity and do so in ways consistent with theorizing on symbolic racism and inter-group conflict. Specifically, Americans place more importance on those components shared with indivduals of the same race. We then analyze how these differing beliefs about national identity influence racial animus. Here, we find robust evidence that individuals who prioritize the ascriptive, exclusive elements of national identity are more racist, while individuals who embrace its most inclusive element are less so. Finally, we reveal that the relationship between conceptions of national identity and racism is moderated substantially by race, and this robust relationship for whites and Latinos is virtually identical.